2016
DOI: 10.2174/0929867323666160405113129
|View full text |Cite
|
Sign up to set email alerts
|

Abscisic Acid: A Phytohormone and Mammalian Cytokine as Novel Pharmacon with Potential for Future Development into Clinical Applications

Abstract: The isoprenoid stress-associated phytohormone abscisic acid (ABA) has recently been recognized to possess multifaceted biological functions in mammals and to exert potent curative effects in a number of clinically relevant human diseases. Studies with human specimens have unequivocally shown that ABA retains its stress-related functional attributes, previously identified in plants, which contribute to enhanced inflammatory defense mechanisms in mammals. Besides, studies performed in animal models revealed prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 0 publications
0
36
0
Order By: Relevance
“…Interestingly, in plants ABA can activate or inhibit AMPK signaling in a tissue dependent manner [69], suggesting that the effects of ABA in the mosquito could vary across tissues. Further, pro- and anti-inflammatory effects of ABA have been reported for acute infection and chronic diseases, respectively, in mammals [70] suggesting that the effects of ABA in mosquitoes could vary depending on the nature of the infecting pathogen or in response to changes in associated microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in plants ABA can activate or inhibit AMPK signaling in a tissue dependent manner [69], suggesting that the effects of ABA in the mosquito could vary across tissues. Further, pro- and anti-inflammatory effects of ABA have been reported for acute infection and chronic diseases, respectively, in mammals [70] suggesting that the effects of ABA in mosquitoes could vary depending on the nature of the infecting pathogen or in response to changes in associated microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, endogenous induction of serum ABA in response to glucose challenge has been shown to stimulate insulin release and is impaired in patients suffering from type 2 diabetes (Bruzzone et al, 2008, 2012a; Ameri et al, 2015). ABA has recently attracted the attention of several research groups as a potential drug lead (Bassaganya-Riera et al, 2010; Sakthivel et al, 2016) because of these promising biological activities. One study has already shown that fruits and vegetables with high ABA contents (such as figs and apricots) are beneficial against hyperglycemia in both rats and humans (Magnone et al, 2015), which makes ABA a potential pharmacognostic drug or nutraceutical.…”
Section: Physiological and Pharmacological Effects Of Aba In Animalsmentioning
confidence: 99%
“…If that is the case, the role of ABA in host-pathogen and mutualistic interactions would be ancient and a universal theme among different organisms and organism interactions. The physiological effects of ABA in animals, especially related to immunity, inflammation and metabolic control, have sparked an interest in utilizing this pathway as a pharmacological target (Sakthivel et al, 2016), which has led to several recent papers on ABA functions in animals. However, the most famous plant hormone with pharmacological effects in humans is salicylic acid (SA).…”
Section: Introductionmentioning
confidence: 99%
“…Besides, ABA activity has also been reported in sponges5, and most recently in mammals with the function of immune modulation and glucose homeostasis regulation67. Thus ABA is also recognized as a candidate for medical applications89.…”
mentioning
confidence: 99%